PENYULUHAN DAN PEMERIKSAAN KESEHATAN SEBAGAI “SCREENING TEST” PENYAKIT TIDAK MENULAR PADA MASYARAKAT DUSUN TOGIHORO, DESA KUSURI KECAMATAN TOBELO BARAT - Blandina, Olivia Asih; Ohoiwutun, Ludyana Veronika; Bungan, Jeversan; Hohedu, Ribka; Kundiman, Marselino (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2021)
This community service was carried out for 1 day for the community in Togihoro, Kusuri Village, West Tobelo District aimed to increasing public knowledge about non-communicable diseases and conduct health checks as a form of screening test to detect uric acid, blood sugar and choleterol levels early. This activity was carried out by lecturers and students of the Hein Namotemo University, Nursing Department. The methods used were counseling and medical examinations. The implementation stage begins with counseling on non-communicable diseases (PTM) delivered by a lecturer in the Nursing Department at Hein Namotemo University, followed by discussion. Then proceed with a health examination which includes checking uric acid levels, blood sugar and cholesterol. The results of the evaluation of health checkup activities show that the community has increased knowledge about non-communicable diseases (PTM) compared to before the education was carried out. The results of health examinations showed that a number of residents of Togihoro, Kusuri Village, West Tobelo District were suffering from non-communicable diseases such as cholesterol, uric acid, and diabetes.